2020
DOI: 10.1007/s00705-020-04732-1
|View full text |Cite
|
Sign up to set email alerts
|

Peste des petits ruminants in Africa: a review of currently available molecular epidemiological data, 2020

Abstract: Small ruminants (e.g., sheep and goats) contribute considerably to the cash income and nutrition of small farmers in most countries in Africa and Asia. Their husbandry is threatened by the highly infectious transboundary viral disease peste des petits ruminants (PPR) caused by peste-des-petits-ruminants virus (PPRV). Given its social and economic impact, PPR is presently being targeted by international organizations for global eradication by 2030. Since its first description in Côte d’Ivoire in 1942, and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 91 publications
0
66
0
Order By: Relevance
“…However, bioinformatics errors or laboratory contamination can lead to false signals of recombination in PPRV [39, 48]. Previous reports have also highlighted the issue of contamination in published PPRV sequences [33, 39, 48, 49], so the most probable explanation is that the recombinant PPRV genomes we identified are the result of laboratory contamination during the process of genome sequencing. However, PPRV recombination cannot be totally ruled out and should be further explored in dedicated infection experiments.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, bioinformatics errors or laboratory contamination can lead to false signals of recombination in PPRV [39, 48]. Previous reports have also highlighted the issue of contamination in published PPRV sequences [33, 39, 48, 49], so the most probable explanation is that the recombinant PPRV genomes we identified are the result of laboratory contamination during the process of genome sequencing. However, PPRV recombination cannot be totally ruled out and should be further explored in dedicated infection experiments.…”
Section: Discussionmentioning
confidence: 94%
“…PPRV is classified into 4 genetically distinct lineages, which can be discriminated based on phylogenetic analysis of short gene regions, often a few hundred nucleotides of the N gene [31, 32]. Lineage IV viruses have dominated both the host range and geographic expansion of PPRV seen in recent years and are now replacing other lineages in many African countries [3336]. Understanding this expansion is critical to mitigate challenges to the PPR GEP and to understand the threat of PPRV to biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Lineage II PPRV in Tanzania may have come from Uganda (12,36), however, the origin of Lineage IV may be difficult to discern as it is widely spread across the world and in East Africa (63). Of the eight countries bordering Tanzania, PPR has been reported in four: Kenya, Uganda, Democratic Republic of Congo and Burundi (64,65). Indeed, the existence of an informal cross border livestock trade in the eastern and southern African regions (66, 67) presents a continuous risk of PPR incursion, persistence and spread among these countries and beyond (51,65,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight countries bordering Tanzania, PPR has been reported in four: Kenya, Uganda, Democratic Republic of Congo and Burundi (64,65). Indeed, the existence of an informal cross border livestock trade in the eastern and southern African regions (66, 67) presents a continuous risk of PPR incursion, persistence and spread among these countries and beyond (51,65,68,69). Studies reviewed show that PPR is endemic throughout Tanzania, and it has had devastating effects on the small ruminant population and the livelihoods of pastoralists across the country over the last several years (36).…”
Section: Discussionmentioning
confidence: 99%
“…Lineage IV is usually found in Asia, and hence, has been termed the Asian lineage [9]. A recent review of currently available molecular epidemiological data was carried out in Africa [10] and showed that since 2008, lineage IV has also been continually identified in Africa [9,11,12].…”
Section: Introductionmentioning
confidence: 99%